On the manufacture of silver-BaCe0.5Zr0.3Y0.16Zn0.04O3−δ composites for hydrogen separation membranes. (22nd March 2015) - Ruiz-Trejo, Enrique; Zhou, Yuning; Brandon, Nigel P.
Abstract Silver- BaCe0.5Zr0.3Y0.16Zn0.04O3−δ (Ag/BCZYZ) composites were investigated due to their potential application as hydrogen separation membranes, with emphasis on their fabrication and characterization. A precursor powder of BCZYZ was prepared via a wet chemical route and characterized by XRD, SEM and dilatometry. The precursor powder was coated with silver using Tollens reaction and then sintered under a variety of conditions. It was possible to obtain dense samples with a low level of non-percolating silver (2 vol%). Silver was present even if sintered at 1300 °C as it remained trapped in the ceramic matrix. The overall conductivity of a dense sample with 2 vol% of silver increased when compared to pure BCZYZ, and in particular the grain boundary resistance decreased considerably. A measurement of the open circuit voltage in fuel cell mode indicates the presence of mixed electronic-protonic conductivity in the composite.